The effect of metal oxide additives on the hydrogen sorption behaviour of magnesium hydride - Croston, Deborah Louise (2007)
MgH2 is considered to be one of the most promising options for a solid state hydrogen storage material. For practical use it is still imperative to find a convenient means of overcoming its slow kinetics and high stability. In this investigation, a range of binary and ternary metal oxides of aluminium, silicon, titanium, and zirconium, as well as Pd-modified Ti02 samples, were prepared and characterised. The prepared oxides were ball milled with MgH2, and the hydrogen sorption behaviour of the ball milled mixtures was investigated using DSC-TGA-MSS, Sieverts and IGA. Thermodynamic parameters including enthalpies and entropies of hydrogen desorption were determined from experimental data, and activation energy calculations along with modelling of the kinetics were used to understand the mechanism and rate-limiting step of dehydrogenation.